Modern anticoagulation with factor Xa inhibitors in oncology: is the gastrointestinal bleeding rate (also) decisive? - Raithel, Martin; Haibach, Martina; Kremenevski, Igor; Arnold, Erich; Ringwald, Jürgen (Zeitschrift für Gastroenterologie, 2022)
The increased risk of thrombosis and bleeding with an active tumor disease is known as the so-called "thrombo-hemorrhagic syndrome", which places high demands on anticoagulation. There are currently 4 randomized, prospective studies on the use of new, non-vitamin K dependent oral anticoagulants (NOAC) for the treatment of venous thromboembolism (VTE) that have occurred in oncology. The FXa inhibitors rivaroxaban, edoxaban and twice apixaban were each used in individual studies versus the standard therapeutic agent dalteparin. Since there is no direct head-to-head comparison of the FXa inhibitors mentioned within a study, the largest study - always compared to dalteparin - was evaluated for each NOAC. The studies were analyzed with regard to their effectiveness, safety, fatal bleeding rates, the risk of gastrointestinal bleeding (GIB) and other differences using descriptive statistics. With dalteparin, the mean VTE recurrence rate was approximately 9% over a 6-month treatment period. All three FXa inhibitors were not inferior to dalteparin in terms of potency. The VTE recurrence rate was - 2.3% lower in edoxaban and apixaban-treated patients and - 5.0% in rivaroxaban-treated patients. In terms of safety, there was an increased rate of severe bleeding (both + 2.4%) for rivaroxaban and edoxaban compared to dalteparin; in particular, the number of GIBs was significantly increased. In contrast, the number of severe bleeding was not increased for apixaban, as was the case for various bleeding types including GIB. In the Apixaban study, the overall rate of severe GIB, which accounted for about 50% of all severe bleeding, and that of clinically relevant non-severe bleeding, were the lowest. The FXa inhibitors are not inferior to the standard therapy with dalteparin in the VTE recurrence rate in oncological patients. The GIB rate appears to be an important predictive factor for the safety of this group of substances, so that tumor location, gastrointestinal risk factors and other individual criteria should be given greater consideration in future therapy decisions for or against an FXa inhibitor.
CRIS-Team WoS Importer:2022-08-05